Determination of Absolute Configuration of Salvic Acid, an Ent-Labdane from Eupatorium Salvia, by Vibrational Circular Dichroism - Urzua-Moll, A; Echeverria-Morgado, J (2012)
The relative stereochemistry at C13 and the absolute configuration of salvic acid, a constituent of the leaves of Eupatorium salvia, were established as the 13-(R)-ent-labdane 1. The results follow from vibrational circular dichroism measurements of the derived O-methyl ether methyl ester 3 which were compared to DFT B3LYP/DGDZVP calculated spectra. The relative stereochemistry of salvic acid at C13 was independently verified by single crystal X-ray diffraction measurements of 1, and of its derived diol 4. © 2012 Elsevier Ltd. All rights reserved.